Protein and RNA dynamical fingerprinting - Niessen, Katherine A; Xu, Mengyang; George, Deepu K; Chen, Michael C; Ferré-D’Amaré, Adrian R; Snell, Edward H; Cody, Vivian; Pace, James; Schmidt, Marius; Markelz, Andrea G (Nature communications, 2019)

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Terahertz spectroscopic analysis of peptides and proteins - Falconer, Robert J; Markelz, Andrea G (Journal of Infrared, Millimeter, and Terahertz Waves, 2012)

NONLINEAR QUANTUM DYNAMICS IN SEMICONDUCTOR QUANTUM-WELLS - Sherwin, M. S.; Craig, K.; Galdrikian, B.; Heyman, J.; Markelz, A.; Campman, K.; Fafard, S.; Hopkins, P. F.; Gossard, A. (Physica D-Nonlinear Phenomena, 1995)
We discuss recent measurements of the nonlinear response of electrons in wide quantum wells driven by intense electromagnetic radiation at terahertz frequencies. The theme is the interplay of quantum mechanics, strong periodic driving, the electron-electron interaction and dissipation. We discuss harmonic generation from an asymmetric double quantum well in which the effects of dynamic screening are important. Measurements and theory are found to be in good agreement. We also discuss intensity-dependent absorption in a 400 Angstrom square quantum well. A new nonlinear quantum effect occurs, in which the frequency at which electromagnetic radiation is absorbed shifts to the red with increasing intensity. The preliminary experimental results are in agreement with a theory by Zaluzny, in which the source of the nonlinearity is the self-consistent potential in the Hartree approximation for the electron dynamics.

FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

Conversion of 124 and 123 + cupric oxide: microstructure and phase diagram - Morris, D. E.; Nickel, J. H.; Markelz, A.G.; Gronksy, R.; Fendorf, M.; Burmester, C. P. (Materials Research Society Symposium Proceedings, 1990)

CONVERSION OF 124 INTO 123+CUO AND 124, 123 AND 247 PHASE REGIONS IN THE Y-BA-CU-O SYSTEM - Morris, D. E.; Markelz, A. G.; Fayn, B.; Nickel, J. H. (Physica C, 1990)

SPECIFIC-HEAT MEASUREMENTS ON SUPERCONDUCTING BI-CA-SR-CU AND TL-CA-BA-CU OXIDES - ABSENCE OF A LINEAR TERM IN THE SPECIFIC-HEAT OF BI-CA-SR-CU OXIDES - Fisher, R. A.; Kim, S.; Lacy, S. E.; Phillips, N. E.; Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Ginley, D. S. (Physical Review B, 1988)